Vero cell technology for rapid development of inactivated whole virus vaccines for emerging viral diseases - P. Noel Barrett; Sara J. Terpening; Doris Snow; Ronald R. Cobb; Otfried Kistner (Taylor & Francis Group, 2017)
Introduction: Rapid development and production of vaccines against emerging diseases requires well established, validated, robust technologies to allow industrial scale production and accelerated licensure of products. Areas covered: A versatile Vero cell platform has been developed and utilized to deliver a wide range of candidate and licensed vaccines against emerging viral diseases. This platform builds on the 35 years' experience and safety record with inactivated whole virus vaccines such as polio vaccine. The current platform has been optimized to include a novel double inactivation procedure in order to ensure a highly robust inactivation procedure for novel emerging viruses. The utility of this platform in rapidly developing inactivated whole virus vaccines against pandemic (-like) influenza viruses and other emerging viruses such as West Nile, Chikungunya, Ross River and SARS is reviewed. The potential of the platform for development of vaccines against other emerging viruses such as Zika virus is described. Expert commentary: Use of this platform can substantially accelerate process development and facilitate licensure because of the substantial existing data set available for the cell matrix. However, programs to provide vaccines against emerging diseases must allow alternative clinical development paths to licensure, without the requirement to carry out large scale field efficacy studies.